The enhanced Aussie Optimism Positive Thinking Skills Program: The relationship between internalizing symptoms and family functioning in children aged 9–11 years old - Kennedy, Patricia; Rooney, Rosanna M.; Kane, Robert T.; Hassan, Sharinaz; Nesa, Monique (Frontiers in Psychology, 2015)
The family context plays a critical role in the health of the child. This was the first study to examine the usefulness of the General Functioning subscale of the Family Assessment Device (FAD-GF) in assessing family functioning and its relationship to internalising symptoms in school-aged children aged between 9 and 11 years of age. Eight hundred and forty-seven Year 4 and 5 students from 13 schools (607 intervention students, and 240 control students) participated in the Aussie Optimism Positive Thinking Skills Program (AO-PTS) - a universal school-based program targeting internalising symptoms. Students rated how ‘healthy’ they perceived their family to be at pre-test and at 6-month follow-up. Although some aspects of validity and reliability could be improved, results indicated that perceptions of family functioning at pre-test were predictive of internalising symptoms at the 6-month follow-up. The FAD-GF therefore showed promise as a potential measure of family functioning for children as young as nine years old. Regardless of children’s pre-test levels of perceived family functioning, no intervention effects were found on the anxiety and depression scales; this finding suggests that child perceptions of family functioning may act as a general protective factor against internalising symptomology.